2004
DOI: 10.1111/j.1365-2958.2004.03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide O antigen status of Yersinia enterocolitica O:8 is essential for virulence and absence of O antigen affects the expression of other Yersinia virulence factors

Abstract: Lipopolysaccharide (LPS) is the major component of the outer membrane of Gram-negative bacteria. Although much attention has been given to the biological effects of its lipid A portion, a great body of evidence indicates that its O chain polysaccharide (O antigen) portion plays an important role in the bacterium-host interplay. In this work we have studied in-depth the role of the O antigen in Yersinia enterocolitica serotype O:8 pathogenesis. We made a detailed virulence analysis of three mutants having diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 85 publications
4
101
0
Order By: Relevance
“…Whilst a rough Y. enterocolitica O:8 mutant exhibited alterations in YadA function, downregulation of inv and ail, and hypermotility due to upregulation of flhDC (Bengoechea et al, 2004), no such changes were observed in the YeO3-DrfaH strain. These discrepancies may be explained by differences between the serotypes.…”
Section: K Leskinen and Othersmentioning
confidence: 93%
“…Whilst a rough Y. enterocolitica O:8 mutant exhibited alterations in YadA function, downregulation of inv and ail, and hypermotility due to upregulation of flhDC (Bengoechea et al, 2004), no such changes were observed in the YeO3-DrfaH strain. These discrepancies may be explained by differences between the serotypes.…”
Section: K Leskinen and Othersmentioning
confidence: 93%
“…All of these virulence determinants are present in BT1b and BT2-5 strains, but absent in BT1A strains (Bottone, 1999). In addition, several key publications have highlighted the key role of LPS and O-antigen variation in Y. enterocolitica pathogenesis (Bengoechea et al, 2003(Bengoechea et al, , 2004Rebeil et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting feature of Y. enterocolitica O antigen is that its production is tightly controlled in response to temperature. Y. enterocolitica produce O-antigen in abundance at 22-25°C, but only very low amounts can be detected at 37°C (Bengoechea et al, 2004;2002). This led to speculations, that the function of YeO:3 adhesion factors might be inhibited by the presence of the distinct YeO:3 O antigen.…”
Section: Serotype Specific Interaction Of Y Enterocolitica With Epitmentioning
confidence: 99%
“…In contrast, O-antigen of YeO:3 is composed of a homopolymer of 6-deoxy-L-altrose linked by α-1,2 glycosidic bonds. The O-antigen and the outer core are both connected to the inner core, resulting in the formation of a branched LPS molecule (Al-Hendy et al, 1991;Bengoechea et al, 2004;Brubaker, 1991). An interesting feature of Y. enterocolitica O antigen is that its production is tightly controlled in response to temperature.…”
Section: Serotype Specific Interaction Of Y Enterocolitica With Epitmentioning
confidence: 99%